The regulatory T cells induction by epicutaneous immunotherapy is sustained and mediates long‐term protection from eosinophilic disorders in peanut‐sensitized mice. Issue 6 (June 2014) - Dioszeghy, V.; Mondoulet, L.; Dhelft, V.; Ligouis, M.; Puteaux, E.; Dupont, C.; Benhamou, P.‐H.
Summary Background Allergen‐specific immunotherapy favours immune deviation from a Th2 to a Th1 response and increases the number of regulatory T cells (Tregs). Epicutaneous immunotherapy (EPIT) of sensitized mice decreases the clinical and the allergen‐specific Th2 responses and increases local and peripheral Foxp3+ Tregs. Objective To investigate the role of Tregs in EPIT and characterize their phenotype and maintenance following EPIT. Methods Tregs were investigated using in vivo depletion or adoptive transfer into BALB/c mice. Tregs were depleted using anti‐CD25 antibody injection during EPIT, and allergen‐specific responses were compared with Sham, EPIT alone and naïve mice. To demonstrate that Tregs can mediate protection by their own, and to study their maintenance following the end of EPIT, CD25+CD4+ Tregs isolated from mice just after or 8 weeks after EPIT were transferred into peanut‐sensitized mice. Foxp3‐IRES‐mRFP mice were transferred with EPIT‐induced Tregs to analyse the induction of host Tregs. Results The anti‐CD25 antibody injection to EPIT mice abrogated the induction of Tregs in spleen and the expression of Foxp3 in oesophagus. This resulted in levels of peanut‐induced eosinophilic infiltration in oesophagus similar to Sham and significantly higher than EPIT. Whereas the transfer of Tregs from Sham‐treated mice demonstrated no effect, the transfer of Tregs isolated just after EPIT prevented peanut‐induced eosinophil infiltration and eotaxin expression and induced Foxp3 in oesophagus. The transfer of Tregs isolated 8 weeks after EPIT suppressed allergen‐specific responses as efficiently as did Tregs isolated just after EPIT and increased spleen Foxp3+ CD25+ CD4+ cells similarly. The use of reporter mice demonstrated an increase in host Tregs. Conclusions These results confirm the Tregs‐mediated mechanism of EPIT and demonstrate the persistence of efficient Tregs during a long period of time after treatment cessation. This suggests that EPIT induces long‐term tolerance in peanut‐sensitized mice.